An Undiagnosed Non Functioning Retroperitoneum Paraganglioma, Complicating A Gynaecological Surgery; A Case Report - AW, Noraziana; B, Hakim; R, Alik; A, Mokhtar (IIUM Medical Journal Malaysia, 2010)
Paragangliomas are uncommon tumors arising from the neuroendocrine elements (chief cells) of the paraganglia and symmetrically distributed along the aorta in close association with the sympathetic chain. Although functional tumors are easier to diagnose due to the clinical findings caused by excess secretion of catecholamines and an elevation of the urinary catecholamine levels, however the diagnosis of nonfunctioning paraganglioma of the retroperitoneum is difficult and only few cases have been made before exploratory laparotomy. Although our patient was initially planned and operated by our gynaecological team, the incidental findings had to involve the general surgeons. She is fortunate that the tumour did not show any features of malignancy nor metastasis, however a long time follow up is needed in case of any possible recurrence.